The structure of a potassium-selective ion channel reveals a hydrophobic gate regulating ion permeation - Patricia S. Langan; Venu Gopal Vandavasi; Wojciech Kopec; Brendan Sullivan; Pavel V. Afonne; Kevin L. Weiss; Bert L. de Groot; Leighton Coates (IUCrJ, 2020)
Protein dynamics are essential to function. One example of this is the various gating mechanisms within ion channels, which are transmembrane proteins that act as gateways into the cell. Typical ion channels switch between an open and closed state via a conformational transition which is often triggered by an external stimulus, such as ligand binding or pH and voltage differences. The atomic resolution structure of a potassium-selective ion channel named NaK2K has allowed us to observe that a hydrophobic residue at the bottom of the selectivity filter, Phe92, appears in dual conformations. One of the two conformations of Phe92 restricts the diameter of the exit pore around the selectivity filter, limiting ion flow through the channel, while the other conformation of Phe92 provides a larger-diameter exit pore from the selectivity filter. Thus, it can be concluded that Phe92 acts as a hydrophobic gate, regulating the flow of ions through the selectivity filter.